PENERAPAN TEKNOLOGI DRYING DENGAN GREEN HOUSE EFFECT UNTUK PENINGKATAN EFISIENSI PRODUKSI DAUR ULANG PLASTIK PADA DR PLASTIK GUNUNGKIDUL - Wahyuningtyas, Dewi; Sukmawati, Paramita Dwi; Purwanto, Yuli (Universitas Mataram, 2024)
DR Plastik is a creative industry in the field of plastic recycling located in Putat Village, Patuk District, Gunungkidul. The number of employees at DR Plastik is 25 people, both as waste sorters, shredding machine operators, washers and administrators. The production capacity of recycled plastic waste is ± 2 tons/day. The plastic waste is processed in the form of dry plastic shreds and resold. Current conditions, the drying process at DR Plastik still takes 2-3 days manually (during the rainy season). This condition makes production run ineffectively and causes product quality to decrease due to uneven drying. The aim of the program is to create drying room technology with a green house effect. This program involves several stages such as coordination with DR Plastik partners regarding the drying room area, procurement of materials and tools, manufacturing a drying room with green house effect, training, and monitoring and evaluation. The result of implementing the program is a drying room with a green house effect measuring 6x10 m2 with a transparent galvalum roof. Galvalum has advantages in terms of resistance to impact, high structural strength, and has good heat absorption capacity, so that the temperature in the building remains comfortable. Apart from that, the production of rainwater channels is centralized in the production process, so that the dried plastic is safe from rainwater. This program shows a significant increase in employee knowledge and skills regarding the use of drying rooms. Apart from that, the drying process has become more effective and efficient from 2-3 days (during the rainy season) to 1 day (during the rainy season) and the production of dry plastic shreds ready for sale has increased by 75%.